Substance P blockade effects on peripheral blood leukocytic reaction in secondary chronic inflammation - O. M. Shevchenko; V. O. Sych (Kazimierz Wielki University, 2019)
In an experimental prospective controlled study the leukocyte response of peripheral blood on the background of blockade of receptors of substance P was studied on the carrageenan model of secondary chronic inflammation in 132 rats. Compared with the natural course of inflammation, at 6 hours there was a significant decrease in total white blood cells count by 1.28 (p<0.05), as well as a significant decrease in the number of polymorphonuclear neutrophils by 4 times (p<0.05) and the number of eosinophils by 3 times (p<0.05) by 10 days. On day 28, there was a significant increase in the number of monocytes in 2 times (p<0,01). The results of the study indicate that in natural conditions of inflammation, substance P stimulates blood leukocytes, as well as prolongs the inflammatory response, and its blocking helps to reduce the inflammatory response.